Low-shrinkage concrete block and preparation method thereof

By using the synergistic effect of HCSA expansion agent and shrinkage agent in concrete blocks and the enhancement of steel fibers and nanosilicon dioxide, the problems of large shrinkage, low strength and high carbon emissions of traditional blocks are solved, and low shrinkage concrete blocks with low shrinkage, high compressive strength and environmentally friendly characteristics are achieved.

CN119797867AInactive Publication Date: 2025-04-11HUIZHOU HONGBAOLONG BUILDING MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510211411.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional concrete blocks have problems such as large shrinkage, low strength, poor thermal performance and high carbon emissions, which lead to prone to cracking, poor thermal insulation effect and short service life.

Method used

The low-shrinkage concrete block formula is adopted, including cement base, lime, aggregate, expansion agent, shrinkage agent, filler and water. Through the synergistic action of HCSA expansion agent and shrinkage agent, the drying shrinkage rate is controlled below 0.02%, and the compressive strength and crack resistance are improved through the enhancement of steel fibers and nano-silica.

Benefits of technology

It achieves low shrinkage, improves compressive strength and crack resistance, improves thermal insulation performance, reduces carbon emissions, has environmentally friendly characteristics, and extends the service life of the block.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797867A_ABST
    Figure CN119797867A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly relates to a low-shrinkage concrete block, which comprises a cement base material, lime, aggregate, an expanding agent, a shrinkage reducing agent, a filler, microcapsules, titanium dioxide particles and water, sulphoaluminate cement and fly ash are adopted as the cement base material, the aggregate is formed by combining quartz sand and ceramsite, and the aggregate is formed by combining lime with ceramsite. The filler comprises steel fibers and nano silicon dioxide, the drying shrinkage rate is extremely low, and due to the addition of the filler, the compressive strength and the crack resistance of the building block are remarkably improved, aggregate is added, the volume weight and the heat conductivity coefficient of the building block are reduced, the heat preservation and heat insulation performance of a building is improved, the freezing resistance of the building block is improved, and the mass loss rate is small; according to the present invention, the cement consumption is reduced, the carbon emission is reduced, the production cost is reduced, the environmental protection characteristic is provided, the production cost of the building block is reduced, and the addition of the microcapsules and the titanium dioxide particles provides the building block with the functions of NOx degradation and VOC removal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, in particular to a low-shrinkage concrete building block and a preparation method thereof. Background Art

[0002] As a widely used building material, the performance of concrete blocks directly affects the quality and durability of buildings. Traditional concrete blocks generally have problems such as large shrinkage, low strength, and poor thermal performance, which leads to easy cracking of the blocks, poor thermal insulation, and short service life. In addition, the production process of traditional blocks uses a large amount of cement and has high carbon emissions, which does not conform to the development trend of green buildings. Therefore, it is of great significance to develop a concrete block with low shrinkage, high strength, excellent thermal performance and environmental protection.

[0003] Therefore, it is necessary to develop a low-shrinkage concrete block with certain environmental protection properties to avoid the problem of shrinkage and cracking of the blocks. Summary of the invention

[0004] Based on this, it is necessary to provide a low shrinkage concrete block with a shrinkage rate controlled below 0.02%, which increases the strength of the block, improves the thermal performance of the block, and has certain environmental protection characteristics.

[0005] The technical solution of the present invention to solve the above technical problems is as follows:

[0006] A low shrinkage concrete block comprises: a cement base material, lime, aggregate, an expansion agent, a shrinkage reducing agent, a filler and water, wherein the proportion of the cement base material is 6%-18%, the proportion of the lime is 5%-8%, the proportion of the aggregate is 60%-70%, the proportion of the expansion agent is 2%-5%, the proportion of the shrinkage reducing agent is 0.1%-0.2%, the proportion of the filler is 2%-4%, and the proportion of the water is 6%-8%.

[0007] Optionally, in one embodiment of the present invention, the cement base material is sulphoaluminate cement or a mixture of sulphoaluminate cement and fly ash.

[0008] Optionally, in one embodiment of the present invention, the aggregate is a combination of quartz sand and any one of crushed stone or expanded clay.

[0009] Optionally, in one embodiment of the present invention, the expansion agent is any one of a UEA expansion agent or a HCSA expansion agent.

[0010] Optionally, in one embodiment of the present invention, the shrinkage reducing agent is a polycarboxylic acid shrinkage reducing agent.

[0011] Optionally, in one embodiment of the present invention, the filler is steel fiber and nano-silicon dioxide.

[0012] A method for preparing a low shrinkage concrete block comprises the following steps:

[0013] Step S1, firstly mix quartz sand and ceramsite, then add cement base material and lime to mix, then add expansion agent and nano silicon dioxide, and the mixing involved is dry mixing;

[0014] Step S2, dissolving the shrinkage reducing agent in 70% of water, and then adding it to the mixed raw material in step S1, and adding the remaining 30% of water by spraying, and the mixing involved is wet mixing;

[0015] Step S3, adding steel fiber to the mixed raw material mixed in step S2 and then performing final mixing to obtain a mixed material;

[0016] Step S4, loading the mixture into the mold, setting the equipment parameters to a vibration frequency of 50Hz-60Hz, an amplitude of 0.5mm-0.7mm, a vibration time of 30s, a molding pressure of 18Mpa-20Mpa, and a holding time of ≥10s, to obtain a low shrinkage concrete block.

[0017] Optionally, in one embodiment of the present invention, the dry mixing time involved in step S1 is 3 minutes.

[0018] Optionally, in one embodiment of the present invention, the wet mixing time involved in step S2 is 5 minutes.

[0019] Optionally, in one embodiment of the present invention, the final mixing time involved in step S3 is 1 min.

[0020] Beneficial effects of the present invention:

[0021] The low shrinkage concrete block provided by the present invention effectively compensates for shrinkage stress through the synergistic effect of an HCSA expansion agent and a shrinkage reducing agent, controls the drying shrinkage rate to be below 0.02%, and significantly improves the compressive strength and crack resistance of the block by adding fillers, the 28-day compressive strength reaches 15-18MPa, and the aggregate reduces the bulk density of the block, the thermal conductivity is as low as 0.25-0.30W / (m·K), and the thermal insulation performance of the building is improved, the frost resistance of the block is significantly improved, the mass loss rate after 50 freeze-thaw cycles is less than 2%, and industrial solid wastes such as fly ash and ceramsite can be used to reduce cement consumption, reduce carbon emissions, and reduce production costs at the same time. The block has environmental protection characteristics and reduces the production cost of the block. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 This is a schematic flow chart of a method for preparing a low shrinkage concrete block according to Example 1 of the present invention;

[0024] Figure 2 This is a compressive strength test data table of a low shrinkage concrete block in Example 5 of the present invention;

[0025] Figure 3 This is a test data table of drying shrinkage rate of a low shrinkage concrete block according to Example 5 of the present invention;

[0026] Figure 4 This is a measurement data table of thermal conductivity of a low shrinkage concrete block according to Example 5 of the present invention;

[0027] Figure 5 This is a frost resistance test data table of a low shrinkage concrete block according to Example 5 of the present invention;

[0028] Figure 6 This is a comparison data table of a low shrinkage concrete block according to Example 5 of the present invention and a prior art block. DETAILED DESCRIPTION

[0029] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0030] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0032] Example 1

[0033] A low shrinkage concrete block comprises: a cement base material, lime, aggregate, an expansion agent, a shrinkage reducing agent, a filler and water. The proportion of the cement base material is 18%, the proportion of the lime is 8%, the lime is required to be completely digested lime, which is used to adjust the alkaline environment and promote the hydration reaction. The lime is digested in advance, the digestion time is ≥48h, and the undigested particles are screened out before use. The proportion of the aggregate is 70%, wherein the proportion of quartz sand is 50%, the proportion of ceramsite is 20%, the proportion of the expansion agent is 3%, the proportion of the shrinkage reducing agent is 0.2%, the proportion of the filler is 4%, the proportion of water is 8%, and the water-binder ratio is 0.45. In this embodiment, the proportion of water is 8%, and the water is tap water, which meets the requirements of JGJ 63-2006.

[0034] In this embodiment, repair microcapsules and phase change microcapsules are added. Epoxy resin is encapsulated in the repair microcapsules, and the proportion of the repair microcapsules is 0.3%-0.6%. When fine cracks appear in the concrete blocks, the microcapsules rupture, and the repair agent flows out to fill the cracks, thereby achieving self-repair and reducing shrinkage deformation caused by crack expansion; the phase change microcapsules are paraffin microcapsules, and the proportion of paraffin phase change microcapsules is 0.5%-1.2%. Its phase change characteristics when the temperature changes absorb or release heat, regulate the internal temperature of the block, reduce the thermal expansion and contraction stress caused by temperature changes, and reduce shrinkage. It also includes rutile titanium dioxide nanoparticles, and the proportion of rutile titanium dioxide nanoparticles is 0.8%-1.5%.

[0035] In this embodiment, the cement base material is a mixture of sulphoaluminate cement and fly ash. Sulphoaluminate cement has a fast hydration speed and high early strength, which can shorten the demoulding and curing time. Sulphoaluminate cement hydrates to form calcium sulfonate, which produces micro-expansion and compensates for concrete shrinkage. The active SiO2 and Al2O3 in the fly ash react with the cement hydration products to form CSH gel, which improves the later strength. The fly ash particles fill the pores of the concrete, improve the density and durability. As industrial solid waste, fly ash replaces part of the cement, reduces carbon emissions and resource consumption. In terms of economy, fly ash is cheap, which can reduce the amount of cement and production costs. Although the unit price of sulphoaluminate cement is high, its usage is small, and it can shorten the production cycle and indirectly reduce costs, which is in line with the development trend of green buildings. Among them, the proportion of sulphoaluminate cement is 8% to reduce the amount of cement and reduce carbon footprint. The fly ash uses Class II fly ash, with a specific proportion of 10%, which is used to replace part of the cement to improve the later strength and durability.

[0036] In the present embodiment, the aggregate is a combination of quartz sand and ceramsite. The aggregate is a combination of quartz sand and ceramsite. Quartz sand has high hardness and can provide a solid skeleton support as a fine aggregate, thereby improving the compressive strength of the block. Ceramsite, as a lightweight aggregate, can reduce the bulk density of the block and reduce the deadweight of the building. The porous structure of ceramsite gives the block excellent thermal performance and reduces the energy consumption of the building. The reasonable combination of quartz sand and ceramsite can optimize the aggregate grading and reduce the risk of shrinkage and cracking. Economically, ceramsite, as an industrial solid waste or artificial lightweight aggregate, has a lower price and can reduce production costs. Quartz sand is abundant in resources and has controllable costs. In combination with ceramsite, it can reduce the amount of cement used. The use of ceramsite can reduce the mining of natural stone and reduce the impact on the environment. The use of combined aggregates can improve the utilization rate of industrial solid waste. The aggregates need to be processed before use. Specifically The particle size of aggregate is controlled at 0.15mm-10mm. The particle size of aggregate is specifically divided into coarse aggregate of 5mm-10mm, medium aggregate of 2mm-5mm, and fine aggregate of 0.15mm-2mm. They are mixed in a ratio of 4:3:3 to build a tighter stacking structure, reduce porosity, improve the volume stability of blocks, and reduce shrinkage risks. Aggregates need to be screened. The proportion of quartz sand is 50%, and the proportion of expanded clay is 20%. In other schemes, the aggregate adopts a combination of crushed concrete and pumice at a ratio of 55%-65%. The particle size of crushed concrete is 1mm-10mm, of which the proportion of pumice is 10%-15%, which can improve lightweight. When the aggregate adopts this combination, the amount of water can be reduced appropriately, because the water demand of pumice crushed concrete is relatively low, which can save water.

[0037] In this embodiment, the expansion agent is HCSA expansion agent, which has a more stable expansion effect, a controllable expansion amount, and a 3% expansion agent ratio. In other schemes, the expansion agent can be MEA expansion agent, and the addition ratio is 1.5%-3%. The later expansion is more stable and the risk of cracking is reduced.

[0038] The shrinkage reducer is a polycarboxylic acid shrinkage reducer, which can reduce capillary stress and reduce drying shrinkage. In this embodiment, the proportion of the polycarboxylic acid shrinkage reducer is 0.2%. In other schemes, the shrinkage reducer can be a modified lignin sulfonate shrinkage reducer. The shrinkage reduction rate of the modified lignin sulfonate is equivalent to that of the polycarboxylic acid shrinkage reducer and has a low environmental cost. If a modified lignin sulfonate shrinkage reducer is used, its proportion is 0.15%-25%, and the sulfonation degree of the modified lignin sulfonate is ≥80%.

[0039] In this embodiment, the fillers are steel fibers and nano-silica. The steel fibers are used to improve the crack resistance and toughness of the blocks. The steel fibers can be copper-plated to enhance the bonding strength between the steel fibers and the cement matrix, so that they can better play a reinforcing role in concrete, effectively inhibit the generation of cracks, and reduce shrinkage. Nano-silica is used to fill micropores, improve density and strength, and nano-silica is made into nano-silica sol. Compared with powder, the sol state can be more evenly dispersed in the cement slurry, more fully participate in the hydration reaction, and improve the early strength and shrinkage resistance of the concrete. Among them, the proportion of steel fiber is 2%, and the proportion of nano-silicon dioxide is 2%. In other schemes, the filler can be a combination of basalt fiber and nano-calcium carbonate, or basalt fiber and nano-calcium carbonate can be mixed with steel fiber and nano-silicon dioxide. Basalt fiber replaces steel fiber, and nano-calcium carbonate replaces nano-silicon dioxide. Nano-calcium carbonate has lower cost and can improve alkali aggregate reaction. The proportion of filler is 3%-5%, of which basalt fiber is 0.8%-1.2%, and nano-calcium carbonate is 2%-3.8%. The length of basalt fiber is 6mm-12mm, and the particle size of nano-calcium carbonate is 30mm-50mm. The prepared blocks have reduced drying shrinkage, but improved compressive strength.

[0040] The blocks in this case show significant improvement in early and late strength in actual use. The compressive strength after 28 days can reach 16-18MPa, the crack resistance and toughness are better, the shrinkage compensation effect is significant, the drying shrinkage rate can be controlled below 0.02%, the thermal conductivity is reduced to 0.25-0.30W / (m·K), the thermal insulation performance is better, the density is improved, and the mass loss rate after 50 freeze-thaw cycles is less than 2%. The cost is relatively high, which is suitable for projects with higher requirements.

[0041] like Figure 1 As shown, a method for preparing a low shrinkage concrete block specifically comprises the following steps:

[0042] Step S1, first mix quartz sand and ceramsite, stir for 1 minute, then add cement base material and lime to mix, then add expansion agent and nano silicon dioxide, stir for 2 minutes, the mixing involved is dry mixing, and the dry mixing time is 3 minutes in total;

[0043] Step S2, dissolving the shrinkage reducing agent in 70% water, adding it to the mixed raw material of step S1, stirring for 3 minutes, adding the remaining 30% water by spraying, stirring for 2 minutes, the mixing involved is wet mixing, and the wet mixing time is 5 minutes.

[0044] Step S3, adding steel fiber to the mixed raw material mixed in step S2 and then performing final mixing, the final mixing time is 1 minute, and stirring for 1 minute after adding the steel fiber to obtain a mixed material;

[0045] Step S4, loading the mixture into the mold, setting the equipment parameters to a vibration frequency of 50Hz-60Hz, an amplitude of 0.5mm-0.7mm, and a vibration time of 30s, i.e., the vibration table parameters; the molding pressure is 18Mpa-20Mpa, and the holding time is ≥10s, i.e., the pressing molding machine parameters, and demolding is performed after standing for 2h to obtain a low shrinkage concrete block.

[0046] When the filler is basalt fiber and nano calcium carbonate, the nano calcium carbonate is premixed with 30% water and ultrasonically dispersed for 20 minutes;

[0047] The building blocks of the present invention also include a curing mechanism in actual use. If a curing agent is used, a film-forming curing agent can be used. Specifically, the first step is pre-curing, the pre-curing temperature is 25±2°C, the humidity is ≥95%, and the time is 6 hours; the second step is steam curing, the steam curing temperature is increased from 50°C to 80°C, the humidity is ≥90%, the time is 12 hours, and the heating rate is <15°C / h; the third step is dry-wet cycle, i.e., immersion in water at 20°C for 2 hours, drying for 22 hours, and a cycle of 7 days.

[0048] In this embodiment, the equipment required includes a crusher, a screening machine, a lime dissolution device, a mixer, an admixture metering system, a fiber dispersion device, a vibrating table, a pressing machine, a steam curing kiln, a dry-wet cycle curing device and a spraying system. The crusher is used to crush large pieces of quartz sand or ceramsite to ensure that the aggregate particle size meets the requirements; the screening machine is used to screen quartz sand and ceramsite to ensure that the aggregate grading is continuous, and the mesh size of the vibrating screen is 4.75 mm; the lime dissolution device is used to completely dissolve the lime, and the mixer is used to evenly mix the dry and wet materials. uniform mixing; admixture metering system, used to accurately meter liquid admixtures such as shrinkage reducers and curing agents, with a metering accuracy of ±0.5%; fiber dispersion equipment, used to ensure that steel fibers are evenly dispersed in the mixture to avoid agglomeration; vibration table, used to make the mixture dense and expel bubbles; pressing machine, which applies pressure to the mixture to form the block body; steam curing kiln, which provides a constant temperature and humidity environment to promote the early strength of the blocks; dry-wet cycle equipment, which simulates the alternating dry-wet environment to improve the durability of the blocks; spray system, which is used to replenish water during the wet curing stage.

[0049] Example 2

[0050] In this embodiment, a low shrinkage concrete block is basically the same as the concrete block of Example 1, except that the proportions of the components are different, specifically: the proportion of cement base is 11%, of which the proportion of sulphoaluminate cement is 6%, the proportion of fly ash is 5%, the proportion of lime is 5%, the proportion of aggregate is 60%, of which the proportion of quartz sand is 45%, the proportion of ceramsite is 15%, the expansion agent is HCSA expansion agent, the proportion of the expansion agent is 2%, the shrinkage reducer is polycarboxylic acid shrinkage reducer, the proportion of the shrinkage reducer is 0.1%, the proportion of filler is 2%, and the proportion of water is 6%.

[0051] Compared with the concrete blocks in Example 1, the concrete blocks in this case have lower early strength, a 28-day compressive strength of about 12-14 MPa, a smaller reinforcement effect of steel fiber and nano-silica, relatively poor crack resistance and toughness, limited shrinkage compensation effect, a drying shrinkage rate of 0.03%-0.035%, a higher block bulk density, a thermal conductivity of about 0.35-0.40 W / (m·K), a lower density, a mass loss rate of about 4-5% after 50 freeze-thaw cycles, and relatively poor long-term durability of the blocks.

[0052] The concrete blocks of this embodiment are prepared by the same preparation method as that of embodiment 1.

[0053] Example 3

[0054] Considering the comprehensive performance and economy of the blocks, it is better to use an intermediate proportion of the components in the block formula, specifically: the proportion of sulphoaluminate cement is 7%, which provides sufficient early strength while controlling costs, and the proportion of fly ash (Grade II) is 8%, which increases the later strength, improves workability and durability, and makes full use of industrial solid waste. The proportion of completely dissolved lime is 6%, which adjusts the alkaline environment and promotes hydration reaction, while avoiding excessive volume instability. The proportion of HCSA high-performance expansion agent is 2.5%, which provides sufficient expansion to compensate for shrinkage while avoiding excessive expansion. The proportion of quartz sand is 48%, which provides solid skeleton support and optimizes aggregate grading. The particle size of expanded clay is 5mm-10mm, and the proportion of expanded clay is 18%, which reduces the bulk density, improves thermal properties, and ensures strength. The proportion of polycarboxylic acid shrinkage reducer is 0.15%, which effectively reduces drying shrinkage while avoiding excessive impact on concrete workability. The proportion of steel fiber is 1.5%, which significantly improves crack resistance and toughness while controlling costs. The proportion of nano-silica is 1.5%, which fills micropores, improves density and strength, while avoiding excessive fluidity. The proportion of water is 7%, and the water-cement ratio is 0.4, which ensures workability and strength.

[0055] The concrete blocks of this embodiment are prepared by the same preparation method as that of embodiment 1.

[0056] Example 4

[0057] In this embodiment, the block formula is basically the same as the above embodiment, except that the HCSA expansion agent is replaced by the UEA expansion agent, and the ceramsite in the aggregate is replaced by crushed stone. When other components remain unchanged, the prepared blocks have different performances, specifically: the expansion rate is slow, the expansion amount is relatively small, the expansion mechanism is mainly to generate ettringite and calcium hydroxide, the expansion effect is weakened in the later stage, the drying shrinkage rate increases from less than 0.02% to 0.025-0.03%, the early strength development is slightly slow, affecting the long-term volume stability, crushed stone, high bulk density--2600-2700kg / m 3 , high thermal conductivity - 1.5-2.0W / (m·K), dense structure, can improve the compressive strength of the block, but the thermal performance is poor, the bulk density of the block is from 1200-1400kg / m 3 Increase to 1800-2000kg / m 3 The thermal conductivity increased from 0.25-0.30W / (m·K) to 0.45-0.50W / (m·K), the compressive strength increased from 15-18MPa to 18-20MPa, the porosity of the crushed stone was poor, the frost resistance of the blocks decreased slightly, and the mass loss rate after 50 freeze-thaw cycles increased from <2% to 3%-4%.

[0058] The formula improvement of this embodiment can increase the proportion of UEA expansion agent to 3%-4%, and add 0.3% magnesium oxide expansion agent to compensate for the later expansion; add 3%-5% vitrified microspheres to replace part of the crushed stone to reduce the thermal conductivity to 0.35-0.40W / (m·K); add 0.02-0.05% air entraining agent to introduce uniform microbubbles to buffer freeze-thaw stress. In terms of cost control, the blocks produced by the replaced formula reduce the cost by 10%-15% compared with the blocks produced by the original formula.

[0059] Example 5

[0060] like Figure 2-6 As shown, in this embodiment, an experimental method for the building blocks made by the present scheme is disclosed, and the corresponding equipment required for the experiment include: a pressure testing machine, a drying shrinkage machine, a freeze-thaw test chamber, a thermal conductivity meter and an electronic balance. The pressure testing machine tests the compressive strength of the building blocks, the drying shrinkage machine measures the drying shrinkage rate of the building blocks, the freeze-thaw test chamber tests the frost resistance of the building blocks, the thermal conductivity meter tests the thermal conductivity of the building blocks, and the electronic balance is used to accurately weigh the raw materials and the mass of the trial pieces. The experimental items specifically include: compressive strength, drying shrinkage rate, frost resistance and thermal conductivity.

[0061] The specific experiment is: prepare 10 standard building blocks, taking 390mm*190mm*190mm as an example: the formula adopts the formula ratio of the above embodiment 3 for trial production, and the total mass of the 10 standard building blocks is 120kg.

[0062] 1. Compressive strength test: the test standard is GB / T4111-2013, the test time is 7 days and 28 days, and the test method is as follows:

[0063] 1. Cut the blocks into 100mm×100mm×100mm specimens.

[0064] 2. Load at a rate of 0.5 MPa / s on the pressure testing machine and record the failure load.

[0065] 3. Calculate compressive strength:

[0066]

[0067] F is the failure load and A is the compressive area.

[0068] The data obtained: compressive strength (Mpa): 7-day data is 10.5±0.8, 28-day data is

[0069] 2. Drying shrinkage test: the test standard is based on JGJ / T70-2009, the test time is 3 days, 7 days, and 28 days, and the test method is as follows:

[0070] 1. Cut the blocks into 40mm×40mm×160mm specimens.

[0071] 2. Measure the initial length (L0) on the drying shrinkage instrument,

[0072] 3. Maintain in an environment of 20±2℃ and 60±5% humidity, and measure length (L t )

[0073] 4. Calculate the shrinkage rate:

[0074]

[0075] 3. Freeze resistance test: the test standard is in accordance with GB / T2542-2012, and the test method is as follows:

[0076] 1. Weigh the blocks after soaking them in water for 48 hours (m0).

[0077] 2. Perform freeze-thaw cycles (freeze at -20°C for 4 hours, thaw at 20°C for 4 hours),

[0078] 3. Weigh after every 25 cycles (m n ), calculate the mass loss rate:

[0079]

[0080] 4. Thermal conductivity measurement, the test standard is GB / T10294-2008, the test method is as follows:

[0081] 1. Cut the blocks into 300mm×300mm×30mm specimens.

[0082] 2. Measure on the thermal conductivity meter and record the heat flux and temperature gradient.

[0083] 3. Calculate thermal conductivity:

[0084] Where Q is the heat flow, d is the thickness, A is the area, and ΔT is the temperature difference.

[0085] 5. Water absorption test: the test standard is in accordance with GB / T 11969-2020, and the test method is as follows:

[0086] 1. Cut the blocks into 100mm×100mm×100mm trial pieces;

[0087] 2. Cool the test piece to room temperature after drying;

[0088] 5. Completely immerse the dry specimen in clean water at 20±2℃, with the water surface 50mm above the specimen; 6. Immersion time: 48h;

[0089] 7. Take out the test piece and wipe off the surface moisture with a damp cloth;

[0090] Water absorption calculation:

[0091]

[0092] Wherein, W is the water absorption rate (%), m1 is the dry mass (g), and m2 is the mass after immersion in water (g).

[0093] Data processing:

[0094] For each test set, the average value of 3 test pieces was taken.

[0095] Record data such as compressive strength, drying shrinkage, mass loss rate, thermal conductivity, etc. Use variance analysis to compare the performance differences of different formulations. Draw a curve chart of performance changes over time to analyze trends.

[0096] Through the above experimental method, the test pieces are tested, such as Figure 2-6 As shown, according to the data, a low shrinkage concrete block of this scheme can better avoid the problem of shrinkage cracking compared with the existing concrete blocks, has an extremely low drying shrinkage rate, and has better compressive strength and crack resistance, improves the thermal insulation performance of the building, and improves frost resistance. It utilizes industrial solid waste such as fly ash and expanded clay, reduces cement consumption, reduces carbon emissions, and reduces production costs. It has environmental protection characteristics and reduces the production cost of blocks.

[0097] In summary, the low shrinkage concrete block of this scheme reduces the drying shrinkage rate to ≤0.02% through the synergistic effect of HCSA high-performance expansion agent and polycarboxylic acid shrinkage reducer. Sulphoaluminate cement hydrates to form calcium sulfonate, which continuously compensates for shrinkage stress; steel fiber and nano-silica enhance the interface transition zone, and the 28-day compressive strength is increased to 15-18MPa; steel fiber disperses shrinkage stress, and the crack width is reduced to <0.1mm. Nano-silica fills micropores and blocks the crack expansion path, and the crack resistance is increased by more than 3 times, extending the service life of the block; the porous structure of ceramsite reduces the thermal conductivity to 0.25-0.30W / (m·K), and nano-silica optimizes the pore distribution, reduces heat convection, and reduces the thermal conductivity by 30-40%, with significant energy-saving effect, which is suitable for exterior wall insulation system. Sulphoaluminate cement provides early strength, shortens demoulding time, reduces shrinkage by 50-70%, and significantly reduces the risk of wall cracking, which is suitable for large-volume concrete and high-rise buildings; ceramsite, the bulk density is reduced to 1200-1400kg / m 3, reducing the building's own weight by 20-30%, reducing foundation load and transportation costs; expanded clay pores buffer freeze-thaw stress, nano-silica has a dense structure, mass loss is less than 2%, and frost resistance is increased by 2-3 times, making it suitable for cold areas; fly ash and expanded clay replace part of the cement and part of the natural aggregate, the utilization rate of industrial solid waste is ≥25%, the cement consumption is reduced to 6-8%, and carbon emissions are reduced by 30-40%, which is in line with the technical development trend of green buildings. The use of sulphoaluminate cement and subsequent maintenance mechanism can shorten the maintenance cycle, improve construction efficiency, and speed up the project progress.

[0098] Example 6

[0099] In this embodiment, the formula of the building block is different from that of the above embodiment. The difference lies in that HC-CSA cement is used to replace the original sulphoaluminate cement, which has higher later strength and more stable shrinkage compensation. 10%-15% of steel slag powder is used to replace part of the quartz sand to improve the utilization rate of solid waste; 20%-25% of construction waste recycled aggregate is used to replace ceramsite to reduce resource consumption; 2%-3% of aerogel powder is added, the thermal conductivity can be further reduced to 0.15-0.20W / (m·K), and 0.1%-0.3% of silane coupling agent is added to reduce the water absorption rate to ≤4%; composite fiber is used, and the composite fiber includes 1% of steel fiber and 0.5% of polypropylene fiber to synergistically improve crack resistance.

[0100] By selecting different raw materials and using them in combination, blocks with different characteristics can be produced, such as: highly environmentally friendly blocks and highly durable blocks.

[0101] Example 7

[0102] The present embodiment discloses a low shrinkage concrete block, comprising: cement base material, lime, aggregate, expansion agent, shrinkage reducing agent, filler, repair microcapsule, phase change microcapsule, anatase titanium dioxide nanoparticles and water, wherein the proportion of cement base material is 6%-18%, the proportion of lime is 8%, the lime is required to be completely digested lime, which is used to adjust the alkaline environment and promote the hydration reaction, the lime is digested in advance, the digestion time is ≥48h, and the undigested particles are screened out before use, the proportion of aggregate is 70%, wherein the proportion of quartz sand is 50%, the proportion of ceramsite is 20%, the proportion of expansion agent is 1.5%-3%, the proportion of shrinkage reducing agent is 0.15%-0.25%, the proportion of filler is 4%, the proportion of water is 8%, the water-binder ratio is 0.45, and in the present embodiment, the proportion of water is 8%.

[0103] The cement base material is a mixture of sulphoaluminate cement and fly ash, wherein the proportion of sulphoaluminate cement is 4%-12%, the proportion of fly ash is 2-6%, the proportion of steel fiber is 0.8%-1.5%, the proportion of nano silicon dioxide is 0.5%-1%, the proportion of basalt fiber is 1%-1.8%, the proportion of nano calcium carbonate is 0.6%-1.2%, the proportion of repair microcapsules is 0.3%-0.6%, the particle size is 50μm-200μm, the repair microcapsules are encapsulated with epoxy resin, which can be replaced by cardanol-based bio-epoxy to increase the bio-based content, the proportion of phase change microcapsules is 0.5%-1.2%, the phase change temperature is 25℃-28℃, the phase change microcapsules are paraffin microcapsules, the proportion of anatase titanium dioxide nanoparticles is 0.8%-1.5%, and 0.5% cellulose nano whiskers can be added to the raw materials to enhance the strength of the microcapsule wall material and reduce breakage.

[0104] The blocks of this embodiment have a 28-day shrinkage value of ≤0.018%, which is 55-65% lower than that of traditional blocks. The mass loss after 75 freeze-thaw cycles is <1.8%. The repair rate of a 0.1mm crack within 7 days in an environment with a humidity of >80% is >75%, and the anti-seepage pressure after repair is restored to 85% of the original value. The NOx degradation rate is 65%-80%, and the 24h effect: the VOC removal rate is >55% for formaldehyde and >40% for benzene. The buffer capacity of the temperature difference between day and night: the temperature difference on the surface of the external wall is reduced by 10℃-15℃. The thermal energy storage density is 18kJ / kg-25kJ / kg, the phase change range is 22℃-28℃, and it has three-level anti-cracking mechanisms, namely: 3 days of expansion agent to compensate for chemical shrinkage, 3 days-14 days of shrinkage reducer to inhibit capillary stress, more than 28 days of epoxy microcapsules to repair cracks during service, crack width control: drying shrinkage cracks ≤0.05mm, load crack self-repair threshold ≤0.2mm, steel fiber / basalt fiber addition ratio is 1.2%-1.8%, improving impact toughness>8kJ / m 2 The pores of ceramsite aggregate with a pore size of 50-200μm buffer stress concentration, rainwater triggers the super hydrophilicity of the titanium dioxide surface to achieve self-cleaning, and the phase change microcapsules absorb / release heat through solid-liquid phase change, reducing air conditioning energy consumption by 12%-18%, extending the maintenance cycle interval, and using a large proportion of industrial solid waste as raw materials to meet the requirements of energy saving and environmental protection.

[0105] The building blocks made using the formula of this embodiment can be used in the fields of conventional construction, marine engineering and ecological curtain walls, and are in line with green building design.

[0106] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0107] The above embodiments only express several embodiments of the present application, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application. Therefore, the protection scope of the patent of this application shall be based on the attached claims.

Claims

1. A low shrinkage concrete block, characterized in that: include: Cement base, lime, aggregate, expansion agent, shrinkage reducing agent, filler and water, wherein the proportion of the cement base is 6%-18%, the proportion of the lime is 5%-8%, the proportion of the aggregate is 60%-70%, the proportion of the expansion agent is 2%-5%, the proportion of the shrinkage reducing agent is 0.1%-0.2%, the proportion of the filler is 2%-4%, and the proportion of water is 6%-8%.

2. A low shrinkage concrete block according to claim 1, characterized in that: The cement base material is sulphoaluminate cement or a mixture of sulphoaluminate cement and fly ash.

3. The low shrinkage concrete block according to claim 1, characterized in that: The aggregate is a combination of quartz sand and any one of crushed stone or ceramsite.

4. The low shrinkage concrete block according to claim 1, characterized in that: The expansion agent is any one of a UEA expansion agent and a HCSA expansion agent.

5. The low shrinkage concrete block according to claim 1, characterized in that: The shrinkage reducing agent is a polycarboxylic acid shrinkage reducing agent.

6. The low shrinkage concrete block according to claim 1, characterized in that: The filler is steel fiber and nano silicon dioxide.

7. A method for preparing a low shrinkage concrete block according to any one of claims 1 to 6, characterized in that: The specific steps include: Step S1, firstly mix quartz sand and ceramsite, then add cement base material and lime to mix, then add expansion agent and nano silicon dioxide, and the mixing involved is dry mixing; Step S2, dissolving the shrinkage reducing agent in 70% of water, and then adding it to the mixed raw material in step S1, and adding the remaining 30% of water by spraying, and the mixing involved is wet mixing; Step S3, adding steel fiber to the mixed raw material mixed in step S2 and then performing final mixing to obtain a mixed material; Step S4, loading the mixture into the mold, setting the equipment parameters to a vibration frequency of 50Hz-60Hz, an amplitude of 0.5mm-0.7mm, a vibration time of 30s, a molding pressure of 18Mpa-20Mpa, and a holding time of ≥10s, to obtain a low shrinkage concrete block.

8. The method for preparing a low shrinkage concrete block according to claim 7, characterized in that: The dry mixing time involved in step S1 is 3 minutes.

9. The method for preparing a low shrinkage concrete block according to claim 7, characterized in that: The wet mixing time involved in step S2 is 5 minutes.

10. The method for preparing a low shrinkage concrete block according to claim 7, characterized in that: The final mixing time involved in step S3 is 1 min.

Citation Information

Patent Citations

  • High-strength self-compacting concrete and preparation method thereof

    CN109293317A

  • Low-shrinkage high-strength self-compacting recycled concrete and preparation method thereof

    CN115073093A

  • Micro-expansion porous aggregate ultra-high performance concrete and preparation method thereof

    CN116217160A

  • High performance hybrid fly ash / calcium aluminate gelling composition for mortar and concrete

    CN116635347A

  • Low-shrinkage anti-freezing concrete and preparation method thereof

    CN119118618A